T cell response to Hu-D peptides in patients with anti-Hu syndrome - Rousseau, A.; Benyahia, B.; Dalmau, J.; Connan, F.; Guillet, J. -G.; Delattre, J. -Y.; Choppin, J. (Journal of neuro-oncology, 2005)
The anti-Hu syndrome is the most common paraneoplastic neurologic syndrome but the exact mechanism of immune mediated neuronal injury remains unknown. Anti-Hu antibodies do not appear to play a pivotal role in the pathogenesis of the disease. To assess cell-mediated immunity, we selected 51 peptides from the Hu-D sequence and tested their ability to bind to six common HLA class I molecules. Stable complexes with purified HLA molecules were obtained with 19/51 (37%) selected peptides. Subsequently, the ability of the 19 HLA-binding peptides to stimulate T cells from 10 patients and 10 control subjects was evaluated by detecting IFN-gamma secretion. An anti-peptide T-cell response was observed in 7/10 Hu-positive patients but also in 3/10 control subjects. Overall, a significant T-cell activation occurred in response to 74% (14 out of 19) of the selected peptides in the Hu-positive patients vs. 16% (3 out of 19) in the control group (p < 0.001). In addition, T cells of patients tested within 3 months of the onset of anti-Hu syndrome responded to 82% (14 out of 17) of assessed Hu-D peptides vs. 37% (7 out of 19) in patients tested 1 year or more after developing the syndrome (p < 0.01). Thus, the present study suggests a role of cellular immunity during the course of anti-Hu syndrome.